Oyster shells as archives of present and past environmental variability and life history traits: A multi‐disciplinary review of sclerochronology methods and applications - Vincent Mouchi; C. Fred T. Andrus; Antonio G. Checa; Mary Elliot; Erika Griesshaber; Niklas Hausmann; Damien Huyghe; Franck Lartaud; Melita Peharda; Niels J. deWinter (Limnology and Oceanography Letters)
Abstract Oysters inhabit a variety of coastal and deep‐sea settings over a wide latitudinal range and have a role as ecosystem engineers. They also represent an important food source for humans since hunter‐gatherer times, which motivates interest in using oyster shells as environmental and life history archives. Still, oysters have often been disregarded in sclerochronology studies, although several methods based on both microtextural and geochemical approaches have successfully been investigated. We review how these methods have been used to improve interpretations of shell records, and we identify knowledge gaps in a variety of disciplines. Those include ecology to study larval dispersal and growth rates; archaeology to determine shell midden constructions and site occupations; and palaeoenvironmental and palaeoclimate reconstructions from tidal to annual timescales. We also suggest standardizing sclerochronology procedures to improve palaeoenvironmental reconstructions and biophysical models on oyster larval dispersal.